2022-RA-464-ESGO A phase i dose escalation and expansion cohort trial of carboplatin and gemcitabine with the ATR inhibitor berzosertib in first or second recurrence platinum sensitive epithelial ovarian, peritoneal, and fallopian tube cancer. (20th October 2022) - Wahner Hendrickson, Andrea E; Foster, Nathan; Corr, Bradley R; Duska, Linda; Markham, Merry J; Butler, Kristina; Girda, Eugenia; Miller, Rachel Ware; Arneson, Katherine; Gano, Katherine; Johnson, Janelle; Shapiro, Geoffrey; et al.
Abstract : Introduction/Background: The combination of carboplatin and gemcitabine is a commonly used regimen for platinum-sensitive recurrent ovarian cancer. Preclinical studies showed that ATR knockdown in ovarian cancer cell lines sensitized to a wide variety of genotoxic stresses, including gemcitabine and cisplatin. A phase II study evaluating the addition of berzosertib to gemcitabine in platinum resistant ovarian cancer revealed an improvement in progression-free survival (PFS). We sought to assess the safety and preliminary efficacy signal of the triple combination therapy in high grade ovarian cancer (NCT02627443 ). Methodology: Eligible participants included women with histologically confirmed high grade serous or endometrioid epithelial ovarian, fallopian tube or peritoneal cancer in first or second platinum sensitive recurrence. Using a standard 3+3 design, participants were treated with carboplatin on day 1, gemcitabine on days 1 and 8, and escalating doses of berzosertib on days 2 and 9 of a 21 day cycle. An additional 22 participants enrolled at maximum tolerated dose (MTD). Tumor biopsies were obtained at 3 different timepoints in the expansion cohort. Results: Thirty-three eligible participants were enrolled across 7 institutions in the US, with 28 eligible patients treated at the MTD (6 during dose escalation, 22 during dose expansion). The MTD was deemed to be carboplatin AUC 4, gemcitabine 640 mg/m 2 and berzosertib 90 mg/m 2 /day with grade 4 thrombocytopenia as the only DLT. A confirmed response was observed in 14/28 (50%) participants. Median progression free survival was estimated to be 15.1 months (95% CI, 9.8-NE). The most common adverse events were cytopenias (96% grade 3–4 hematologic adverse event). Translational correlates from the expansion cohort are underway. Conclusion: The MTD of the triple combination was established and the study met its secondary endpoint of initial efficacy; however, significant cytopenias were noted with this regimen, which may limit further development.